2010
DOI: 10.1183/09031936.00178709
|View full text |Cite
|
Sign up to set email alerts
|

Stress failure and high-altitude pulmonary oedema: mechanistic insights from physiology

Abstract: H igh-altitude pulmonary oedema (HAPE) is a potentially fatal altitude illness affecting individuals within 2-4 days of rapid ascent to altitudes above 3,000 m. Although a minority of high-altitude travellers develop HAPE [1], there is some suggestion that many develop subclinical fluid accumulation without overt alveolar flooding [2]. The inciting mechanism of the injury to the lung in HAPE still generates some controversy. However, there is an evergrowing body of evidence that mechanical injury to the pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…However, it has also been argued in literature that initial damage to blood-gas barrier because of ‘stress failure’ is self limiting owing to the propensity for quick closure of this barrier after pressure reduction [23]. This strongly suggests the existence of confounding parallel factors complementing initial stress failure for clinical presentation of HAPE which may arise from conjunction of multiple factors besides capillary stress failure [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has also been argued in literature that initial damage to blood-gas barrier because of ‘stress failure’ is self limiting owing to the propensity for quick closure of this barrier after pressure reduction [23]. This strongly suggests the existence of confounding parallel factors complementing initial stress failure for clinical presentation of HAPE which may arise from conjunction of multiple factors besides capillary stress failure [24].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular injury is usually induced by factors such as altered shear stress, oxidative stress, cytokine, and vascular tone modulators such as endothelin-1, angiotensin II amongst others . Notwithstanding the limitation of single time point study which is less likely to suggest cause/consequence relationship between various events, our global expression profiling for HAPE and acclimatized individuals evoked several interesting mechanistic possibilites besides generating molecular evidence for well known physiological processes involved in HAPE [23], [25]. We observed multiple pathways to be modulated under these conditions which appear to be reminiscent of three broad physiological processes: 1) regulation of capillary pressure (stress failure), 2) modulation of barrier function (endothelial permeability/dysfunction) and 3) differential regulation of hypoxia sensing/response pathways.…”
Section: Discussionmentioning
confidence: 99%
“…These adaptations should significantly improve O 2 uptake and transport at high altitudes, and may contribute to this species' ability to climb thousands of meters of elevation without acclimatization. This feat is particularly impressive when considering that humans could suffer dizziness, altitude sickness, high-altitude pulmonary edema (HAPE) (17), and possibly even death when faced with a similarly extreme change in elevation. In the present study, we detail how the transHimalayan migration of bar-headed geese is achieved and provide insights into their aerobic flight capacity.…”
mentioning
confidence: 99%
“…BMP-2, bone morphogenetic protein-2; 5-HT, 5-hydroxytryptamine; MAP, mean arterial pressure; SaO 2 , percent arterial oxygen saturation; HAPE-p, HAPE patients; HAPE-f, HAPE free sojourners. (Hopkins et al, 2005;West et al, 1991;Hopkins, 2010) and animals at HA (West et al, 1995). It was reported that differential expression of 5-HTT under hypoxia altered the 5-HT function (Machado et al, 2006;Eddahibi et al, 2001), causing pulmonary vessel remodeling (Machado et al, 2006;MacLean et al, 1996;Lee et al, 1994).…”
Section: Discussionmentioning
confidence: 97%